2023
DOI: 10.1007/s40123-022-00644-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Significant Axial Shortening in Myopic Children After Repeated Low-Level Red Light Therapy: A Retrospective Multicenter Analysis

Abstract: Introduction: Myopia is recognized as a progressive eye disease. The aim of this study was to evaluate the frequency and associated factors of clinically significant axial length (AL) shortening among myopic children following repeated low-level red light (RLRL) therapy. Methods: The clinical data that were collected for the myopic children aged 3-17 years who received an RLRL therapy delivered by homeuse desktop light device that emitted light at 650 nm for at least 1 year, were reviewed. The clinical data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
7
9
0
Order By: Relevance
“…As shown in Table 5 , those results were consistent with our previous report and the studies of Xiong et al 3 , 4 , 20 . It was shown that myopia among children could be controlled or reversed to some extent by PBM therapy, resulting in a mean decrease in the AL.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As shown in Table 5 , those results were consistent with our previous report and the studies of Xiong et al 3 , 4 , 20 . It was shown that myopia among children could be controlled or reversed to some extent by PBM therapy, resulting in a mean decrease in the AL.…”
Section: Discussionsupporting
confidence: 93%
“…As one of the most effective interventions compared with other interventions 12 18 , 20 , 21 , we found evidence supporting our hypothesis that the progression of myopia as measured by the AL is reversible using PBM therapy twice a day.…”
Section: Discussionsupporting
confidence: 85%
“…In animal studies, the duration of red light exposure was generally for the entire waking period (12-14 h per day), while protocols in children use 3 min of red light exposure twice a day. Since 2021, over 24 papers have been published on red light therapy for myopia, [2][3][4][5][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] including three review papers. [27][28][29] Eyerising International, manufacturer of the Eyerising Myopia Management Device, advertises the instrument for use in children as young as 3 years old, with online claims that over 100,000 children have been or are currently being treated.…”
Section: Red Light Instruments For Myopia Exceed Safety Limits Lisa A...mentioning
confidence: 99%
“…In some cases, axial shortening has been reported. 3,25 Wang et al 3 reported that 22% of children experienced axial shortening greater than five microns after 12 months of LLRL therapy.…”
Section: Red Light Instruments For Myopia Exceed Safety Limits Lisa A...mentioning
confidence: 99%
See 1 more Smart Citation